Vibration Control in Cable Robots Using a Multi-Axis Reaction System - Rushton, Mitchell (University of Waterloo, 2016)
The primary motivation of this thesis is to develop a control strategy for eliminating persistent vibrations in all six spatial directions of the end effector of a planar cable-driven parallel robotic manipulator. By analysing the controllability of a cable-driven robot dynamic model, the uncontrollable modes of the robot are identified. For such uncontrollable modes, a new multi-axis reaction system (MARS) is developed. The new MARS that is attached to the end effector is made of two identical pendulums driven by two servo motors. A decoupled PD controller strategy is developed for regulating controllable modes and a hierarchical sliding mode controller is developed for controlling the remaining modes of the cable robot using MARS. The performance of both controllers is studied and shown to be effective in simulation. The controllers are then implemented on an experimental test setup of a planar cable-driven manipulator. Both controllers are shown to completely eliminate the end effector vibrations.
Keywords: robotics; control; vibration; cable-driven